2016
DOI: 10.1038/ncomms11075
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell RNA sequencing reveals molecular and functional platelet bias of aged haematopoietic stem cells

Abstract: Aged haematopoietic stem cells (HSCs) generate more myeloid cells and fewer lymphoid cells compared with young HSCs, contributing to decreased adaptive immunity in aged individuals. However, it is not known how intrinsic changes to HSCs and shifts in the balance between biased HSC subsets each contribute to the altered lineage output. Here, by analysing HSC transcriptomes and HSC function at the single-cell level, we identify increased molecular platelet priming and functional platelet bias as the predominant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
253
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 274 publications
(278 citation statements)
references
References 43 publications
25
253
0
Order By: Relevance
“…Subsequent analysis of the murine populations, separating the bipotent m-pMegE signature into megakaryocytic (m-MkP) and erythroid (mpreCFU-E) signatures, displayed an association of aged m-HSC with both megakaryocytic signature ( Fig 4F) and with erythroid signature (Fig 4G). Finally, and in agreement with previous findings in humans [30] and mice [5,7,18,19,21], we observed a distinct age-associated downregulation of lymphoid-affiliated genes in h-and m-HSCs (Figs 3A, 3D, 4E and 4I), decreased frequencies of phenotypic h-and m-CLPs (Fig 1B and 1D), as well as decreased lymphoid output from h-HSC in vitro (Fig 2C).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Subsequent analysis of the murine populations, separating the bipotent m-pMegE signature into megakaryocytic (m-MkP) and erythroid (mpreCFU-E) signatures, displayed an association of aged m-HSC with both megakaryocytic signature ( Fig 4F) and with erythroid signature (Fig 4G). Finally, and in agreement with previous findings in humans [30] and mice [5,7,18,19,21], we observed a distinct age-associated downregulation of lymphoid-affiliated genes in h-and m-HSCs (Figs 3A, 3D, 4E and 4I), decreased frequencies of phenotypic h-and m-CLPs (Fig 1B and 1D), as well as decreased lymphoid output from h-HSC in vitro (Fig 2C).…”
Section: Discussionsupporting
confidence: 92%
“…Regardless, the lineage skewing with murine HSC aging has been linked to an upregulation of myeloid-specific genes and a downregulation of lymphoid-specific genes [11][12][13][14][15]18], although many of previous transcriptome analyses were based on a selection and manual curation of lineage-associated genes. By contrast, recent global transcriptome analysis of single HSCs based on more objectively defined lineage-affiliated transcription programs revealed a molecular and functional platelet bias, rather than a My-bi, in aged murine HSC [21].…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…Projection of young and old HSCs in C57BL/6 and DBA/2 mouse strains 43 and Vwf-EGFP mice 33 showed that both young and old HSCs cluster together with LT-HSCs from our data set, with old HSCs forming a tighter cluster suggestive of a more homogeneous population. Therefore, this analysis not only demonstrates that our large expression atlas permits robust comparisons between single-cell data sets generated in different labs, it also reveals a consistent phenotypic change of old HSCs in both studies, in which old stem cells are more concentrated in what seems to be the core HSC territory of the diffusion map.…”
Section: Visualizing Gene Expression Along the Continuum Of Hspc Diffmentioning
confidence: 72%
“…Single-cell RNA sequencing (scRNA-seq) allows high-resolution whole-transcriptome profiling of individual cells and direct analysis of subpopulations of cells from a larger heterogeneous population. [23][24][25][26][27][28][29][30][31][32][33] Gain or loss of chromosomes should lead to over-or underexpression of genes located on the affected chromosomes. 34 Concomitant increases and decreases in chromosome-wide gene expression levels could be used to infer chromosome copy numbers by scRNA-seq.…”
Section: Introductionmentioning
confidence: 99%